Shifting Kenya's Private Sector into Higher Gear : A Trade and Competitiveness Agenda - World Bank Group (World Bank, Washington, DC, 2016)
Shifting Kenya’s private sector into higher gear: a trade and competitiveness agenda’ was born out of the World Bank’s Trade and Competitiveness (T&C) Global Practice recent stock taking of its work in Kenya. This was part of a Programmatic Approach that aimed to organize T&C’s knowledge, advisory, and convening services to address Kenya’s development challenges in the private sector space. By Sub-Saharan African standards, Kenya has a large private sector, which accounts for around 70 percent of total formal employment. As a result, the dynamics of the private sector are a key determinant of the trajectory of the Kenyan economy. The country’s product market regulations a restrictive for domestic competitors and foreign entrants, and the actions of cartels and behavior of dominant firms across sectors undermines competition and hurts consumers. The Kenyan Government recognizes these challenges and has invested significantly in unlocking these bottlenecks with impressive results so far and several important laws passed. Additional efforts to ease regulatory constraints and expedite important legislative changes could improve the investment climate at national and county levels.